Faktor Teknologi, Organisasi, dan Lingkungan pada Penerapan Akuntansi Digital serta Dampaknya Terhadap Kinerja UMKM - Aryanto Aryanto; Naila Hanum; Rafi Syaefudin (Owner : Riset dan Jurnal Akuntansi, 2023)
Technological advances and intense business competition require MSME actors to be able to take advantage of technology in managing their business, one of which is by applying digital accounting. The factors that will be analyzed in this study use the Technology-Organization-Environment (TOE) Framework. The study was conducted on MSME actors in Tegal City with a sampling technique in the form of purposive sampling. The research was obtained in the form of primary data with a collection technique through a questionnaire with a total of 96 MSME actors as respondents. The data that has been collected was analyzed using WarpPLS 7.0. The results show that relative advantage, compatibility, owner commitment, competitive pressure, and government support have a significant effect on the application of digital accounting, and the application of digital accounting has a significant effect on the performance of MSMEs. Meanwhile, organizational readiness has no significant effect on the application of digital accounting. The results of this study are expected to be used by the government as consideration for policy-making related to the development of a digital financial ecosystem for MSMEs in the City and Regency of Tegal.